Kilka uwag o aktualności filozofii metafizycznej - Borda, Michał; Tetela, Rafał (Poznańskie Studia Teologiczne, 2017)
The article discusses the characteristics of a philosophical and cultural dispute with metaphysics and about metaphysics itself. The criticism of metaphysics and its revival in the nineteenth and twentieth centuries is discussed here. In the first part, the most important philosophical directions dealing with issues of metaphysics are presented: metaphysical idealism, anti-metaphysical positivism and neo-positivism, analytic philosophy versus metaphysics on the example of L. Wittgenstein, the revision of the metaphysical tradition and new investigations in metaphysics. The second part of the article concerns the picture of natural metaphysics including the mathematical-empirical method of researching the world. In the conclusion of the article, a thesis is put forward on searching for new metaphysics which will include a wider sphere of rationality and existential and spiritual experience.